Best Practice Recommendations for the Retention of Radiotherapy Records. Issue 11 (November 2017) - Lockhart, E.; Bak, K.; Schreiner, L.J.; Hodgson, D.C.; Gutierrez, E.; Warde, P.; Sharpe, M.B.
Abstract: This paper offers best practice recommendations for the maintenance and retention of radiotherapy health records and technical information for cancer programmes. The recommendations are based on a review of the published and grey literature, feedback from key informants from seven countries and expert consensus. Ideally, complete health records should be retained for 5 years beyond the patient's lifetime, regardless of where they are created and maintained. Technical information constituting the radiotherapy plan should also be retained beyond the patient's lifetime for 5 years, including the primary images, contours of delineated targets and critical organs, dose distributions and other radiotherapy plan objects. There have been increased data storage and access requirements to support modern image-guided radiotherapy. Therefore, the proposed recommendations represent an ideal state of radiotherapy record retention to facilitate ongoing safe and effective care for patients as well as meaningful and informed retrospective research and policy development. Highlights: Health records should be retained beyond the patient's lifetime +5 years. Technical information should be retained beyond the patient's lifetime +5 years. Appropriate data retention practices are essential to patient safety and care. Recommendations facilitate safe, effective care and retrospective research.